2005 IEEE Engineering in Medicine and Biology 27th Annual Conference 2005
DOI: 10.1109/iembs.2005.1615458
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Cardiac Information From Optical Flow Using Four Dimensional Ultrasound

Abstract: Quantitative analysis of cardiac motion is of great clinical interest in assessing ventricular function. Real-time 3-D (RT3D) ultrasound transducers provide valuable three-dimensional information, from which quantitative measures of cardiac function can be extracted. Such analysis requires segmentation and visual tracking of the left ventricular endocardial border. We present results based on correlation of four-dimensional optical flow motion for temporal tracking of ventricular borders in three dimensional u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
2
2
2

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 13 publications
1
10
0
Order By: Relevance
“…A sample result from one data set is shown in Figure 2. The time course of RMSE for this data set is graphed in Figure 2a, which shows small absolute errors (below 0.07 ~ 7%) despite error accumulation as previously observed in (Duan, Angelini 2005). Time courses of the LV volumes estimated from manual tracing (solid line) and tracking (dashed line) are shown in Figure 2b.…”
Section: Resultssupporting
confidence: 64%
See 1 more Smart Citation
“…A sample result from one data set is shown in Figure 2. The time course of RMSE for this data set is graphed in Figure 2a, which shows small absolute errors (below 0.07 ~ 7%) despite error accumulation as previously observed in (Duan, Angelini 2005). Time courses of the LV volumes estimated from manual tracing (solid line) and tracking (dashed line) are shown in Figure 2b.…”
Section: Resultssupporting
confidence: 64%
“…The proposed method was not being applied as a segmentation tool, but used as a surface tracking tool for a given segmentation method. No additional reinitialization or forward-and-backward tracking as proposed in (Duan, Angelini 2005) was needed, due to high image quality provided by the open-chest acquisition setup.…”
Section: Methodsmentioning
confidence: 99%
“…Although initial work was primarily concerned with imaging the axial (along the ultrasound beam) strain field, several techniques have been developed to compute two- and three-dimensional strains (Baraldi et al, 1996; Crosby et al, 2009; Duan et al, 2005; Kaluzynski et al, 2001; Konofagou and Ophir, 1998; Papademetris et al, 2001; Suffoletto et al, 2006). Increasing the dimensionality of the strain measurement is of particular importance in cardiac imaging since heart motion is a complex, three-dimensional phenomenon.…”
Section: Introductionmentioning
confidence: 99%
“…Meunier [3] analyzed the performance of 3D speckle tracking using simulated ultrasound images. Our group [6, 7] has shown that using a correlation-based optical flow method, myocardial motion fields can be estimated, from which directional displacements and strains can be reliably computed. In order to further evaluate the potential of this method, in this study, strain values estimated by our tracking method on ischemic regions were directly compared to “gold standard” strain measures acquired via sonomicrometry at the same locations, and recorded simultaneously during the ultrasound acquisition.…”
Section: Introductionmentioning
confidence: 99%